The Commercial Aspect of the Fetish and Its Secret. The art of profiling objects among West African antique dealers - (:unkn) unknown (My University, 2019)
In this paper I examine the work of West African antique dealers, who act as key intermediaries on the market of African art, by looking at how some magical-ritual objects are turned into commodities and works of art simultaneously. I describe how West African dealers use the concept of “fetish,” within which two apparently contradictory strategies of devaluation and valuation of these paradoxical objects are at work. Depending on the context and their contacts, antique dealers put stress on differences between the magic/ritual sphere and the art market; at other times, they highlight instead the affinities between their own skills and those of the “fetishers,” and more generally between commodities and “fetishes” (which Karl Marx had already perceived). The introduction of “fetishes” on the art market thus provides a way to understand how they acquire their value through a process which plays on their triple potential as magical-ritual objects, as commodities, and as works of art.
Keywords: African Research